2002
DOI: 10.1094/mpmi.2002.15.11.1173
|View full text |Cite
|
Sign up to set email alerts
|

Flagella-Driven Chemotaxis Towards Exudate Components Is an Important Trait for Tomato Root Colonization by Pseudomonas fluorescens

Abstract: Motility is a major trait for competitive tomato root-tip colonization by Pseudomonas fluorescens. To test the hypothesis that this role of motility is based on chemotaxis toward exudate components, cheA mutants that were defective in flagella-driven chemotaxis but retained motility were constructed in four P. fluorescens strains. After inoculation of seedlings with a 1:1 mixture of wild-type and nonmotile mutants all mutants had a strongly reduced competitive root colonizing ability after 7 days of plant grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
329
1
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(348 citation statements)
references
References 38 publications
9
329
1
9
Order By: Relevance
“…1). Again, this finding could reflect differences in levels of key attractants in the two exudates that could conceivably play a role in host selection because chemotaxis plays an important role in successful colonization of the rhizosphere (21,(24)(25)(26)(27)(28). Some genes encoding proteins with functions previously implicated in microbial-plant interactions were down-regulated in response to both root exudates (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…1). Again, this finding could reflect differences in levels of key attractants in the two exudates that could conceivably play a role in host selection because chemotaxis plays an important role in successful colonization of the rhizosphere (21,(24)(25)(26)(27)(28). Some genes encoding proteins with functions previously implicated in microbial-plant interactions were down-regulated in response to both root exudates (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, we see that the two-component system, chemotaxis family, response regulator involved in bacterial chemotaxis is significantly expressed late in plant development and its expression positively correlates with the root exudates glycine and xylitol (Supplementary Tables S3 and S4). Interestingly, PGPRs and endophytic bacteria show chemotaxis towards glycine (Gaworzewska and Carlile, 1982;de Weert et al, 2002;Gupta Sood, 2003), while the non-symbiotic nitrogen-fixing bacteria Azotobacter vinelandii shows chemotactic behavior towards xylitol (Haneline et al, 1991). This provides an additional mechanism for the plants ability to manipulate and orchestrate the rhizosphere microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrating the close ties root exudates have on the microbial composition of the rhizosphere is mounting (Broeckling et al, 2008;Badri et al, , 2013aMicallef et al, 2009b;Chaparro et al, 2012Chaparro et al, , 2013, whereby many chemicals present in root exudates act as substrates, chemotactic or signaling molecules to orchestrate changes in microbial composition (Shaw, 1991;de Weert et al, 2002;Jain and Nainawatee, 2002;Horiuchi et al, 2005;Bais et al, 2006;Badri and Vivanco, 2009;Neal et al, 2012;Badri et al, 2013a). Recently, it was reported that the composition of Arabidopsis root exudates change following a plant developmental gradient (Chaparro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…de Weert et al (2002) established that motility in Pseudomonas is a major trait for root colonization, and the organic acids such as malic acid and citric acid are among major chemo-attractants for P. fluorescens in the tomato rhizosphere. This study is supported by Choi et al (2006) that biofilm formation and swarming motility may contribute to bacterial colonization and stable maintenance of antifungal compounds on plant surface.…”
Section: Resultsmentioning
confidence: 99%